Synthesis and characterization of hypercrosslinked hydroxyl functionalized co-polymer beads - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (European Polymer Journal, 2014)
Hydroxyl functionalized beaded copolymers were synthesized from 2-hydroxy ethyl methacrylate by suspension polymerization using two different crosslinking agents (EDMA, DVB) and diluents (1,1,2,2-tetrachloroethane, 1,2-dichlorobenzene). Microporous beads with high surface area were successfully synthesized and characterized by different techniques. Maximum surface area obtained was 564 m(2)/g bearing uniform, spherical as well as non-aggregation images of beads. Thermal properties such as DTG and DSC reveal that, type of crosslinker (flexible/rigid) is major while its concentration is minor parameter that affect decomposition and softening temperature of copolymer. Swelling ratio of copolymer beads was examined as a function of crosslinker and crosslink density. Swelling behavior is in accordance with copolymer-solvent interaction parameter. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Copolymer; Morphology; surface area; Suspension polymerization; Swelling ratio

Synthesis and characterization of thermotropic liquid crystalline polyimides - Mane, Sachin; Rajan, C. R.; Ponrathnam, Surendra; Chavan, Nayaku (Bulletin of Materials Science, 2015)
Non-symmetrical and linear dyad-based mesogens were synthesised containing imine or ester bridging group. In the present work, due to the absence of branching in diamine-based mesogen, the structure has-rigidity inversely imine/ester bridging groups between two benzene rings imparts-flexible property to the mesogen and consequently rigid-flexible property has been balanced. The synthesised mesogens were characterized by different techniques including nuclear magnetic resonance and Fourier transform infrared spectroscopy. Liquid crystalline polymers (LCPs) were synthesised using pyromellitic dianhydride and 4-[(4-aminobenzylidene)amino]aniline or 4-aminophenyl-4-aminobenzoate. Subsequently, thermotropic liquid crystalline polymers (TLCPs) have also been evaluated to obtain optical microscopy textures at different temperatures which demonstrated interesting and notable changes. It is worth noting that marble-like textures were observed upto 200A degrees C.
Keywords: Diamine; liquid crystalline polymer; mesogen; optical microscopy textures; pyromellitic dianhydride

Selective solid-phase extraction of metal for water decontamination - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (Journal of Applied Polymer Science, 2016)
Metal-contaminated industrial effluent is a major concern for human health. Therefore, the removal of metal is of primary importance. In this study, metals were selectively extracted from water. Selective metal recovery was studied with a crown-ether-based polymer, wherein the selectivity was observed for strontium over lead. Parameters influencing the metal recovery, such as the contact time, adsorbent dosage, and metal-ion concentration, were evaluated. Interestingly, the adsorption rate of strontium was exponentially increased for the initial 4 h, and lead was adsorbed exponentially after 6 h. Notably, 98% strontium adsorption and 64% lead adsorption were obtained in 24 h. The Langmuir adsorption isotherm was in good agreement and demonstrated that the reactive sites of the adsorbent were homogeneous with monolayer metal adsorption with an adsorbent. The Freundlich adsorption isotherm was not obeyed by both metals. The pseudo-first-order and pseudo-second-order kinetics indicated that strontium was adsorbed by chemisorption and lead was adsorbed by physisorption. (c) 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 132, 42849.
Keywords: Adsorption; copolymers; crosslinking; kinetics; radical polymerization

Synthesis of 2-phenoxy-2-phenylethyl acrylate and copolymerization with 2-phenylethyl acrylate: estimation of monomer reactivity ratios, thermal and optical properties - Ghorpade, Ravindra V.; Ponrathnam, Surendra; Chavan, Nayaku (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2016)
A new aromatic based monomer 2-phenoxy-2-phenylethyl acrylate (PPEA) was synthesized. Copolymers of PPEA with 2-phenylethyl acrylate (PEA) were prepared by free radical polymerization. The reactivity ratios were estimated using various graphical methods. Structural parameters of the copolymers were obtained by calculating the dyad monomer sequence fractions and the mean sequence length. Optical properties of polymers such as refractive indices and UV-Visible absorption were investigated. The glass transition temperature and thermal degradation behavior of the copolymers were studied. Combined with the RI, transparency and thermal properties, prepared copolymers hold great promise as materials for intraocular lens applications.
Keywords: 2-Phenoxy-2-phenylethyl acrylate; 2-phenylethyl acrylate; copolymerization; Optical properties; reactivity ratios; Thermal properties